Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking an d working politically” (TWP) has coalesced into a “second orthodoxy” a bout how to take context into account when implementing development in terventions. This approach stresses the importance of obtaining a bett er understanding of the local context (“thinking politically”) in orde r to support local actors to bring about sustainable developmental cha nge (“working politically”). However, the evidence base to justify thi s new approach remains thin, despite a growing number of programmes wh ich purport to be implementing it. Officials in development agencies s truggle with putting it into practice and it is unclear how TWP differ s—or not—from similar approaches, such as Problem Driven Iterative Ada ptation (PDIA) and Doing Development Differently (DDD). This Special I ssue sheds light on what TWP means in practice by examining a set of i nitiatives undertaken by both development partners and government depa rtments in Nigeria, the Occupied Palestinian Territories, China and In dia. This overview article outlines, in brief, each of the Special Iss ue's four papers and then draws out five lessons—for funders and for p ractitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA ) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to suppo rt local ownership—not just “agreement ownership” (between a donor age ncy and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key loc al actors driving change; (4) the need for a more effective set of too ls for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the polit ical economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysi s takes into account the political economy of donors as well as that o f the local context. We conclude with a set of operational recommendat ions for donors and implementors, as well as suggestions of avenues fo r further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically